Pengembangan Multimedia Pembelajaran Interaktif Berbasis Platform Genially pada Materi Perangkat Keras Komputer (Hardware) Pelajaran Informatika di Kelas VII SMPN 3 Kuningan - Firjatullah, Rizal; Fitriah Nurjanah, Hifni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aimed to design and develop interactive learning multimedia utilizing the Genially platform to support the teaching of hardware concepts for seventh-grade junior high school students. The research adopted a Research and Development (R&D) approach, employing the Alessi and Trollip model, which encompasses the planning, design, and development phases. Participants included subject matter experts, media experts, and 30 students from SMPN 3 Kuningan. Data were gathered through observations, interviews, questionnaires, and pretest–posttest assessments, and analyzed using descriptive statistics, percentage scores, and Likert-scale evaluations. Validation results demonstrated a high level of feasibility (84%), with positive learner responses of 75.25% in the small-group trial and 87% in the large-group trial. Furthermore, posttest scores showed a statistically significant improvement compared to pretest scores. These findings indicate that the Genially-based multimedia is both pedagogically feasible and effective in enhancing students’ comprehension of hardware-related content.